Effect of konjac glucomannan on gut microbiota from hyperuricemia subjects in vitro: fermentation characteristics and inhibitory xanthine oxidase activity - Deng, Jie; Zhou, Kai; Feng, Caimin; Bao, Yilu; Zhang, Zhiming; Luo, Wenfeng; Li, Meiying (Frontiers in Nutrition, 2024)
Background The disorder of uric acid metabolism is closely associated with gut microbiota and short-chain fatty acids (SCFAs) dysregulation, but the biological mechanism is unclear, limiting the development of uric acid-lowering active polysaccharides. Konjac glucomannan (KGM) could attenuate metabolic disturbance of uric acid and modulate the gut microbiota. However, the relationship between uric acid metabolism and gut microbiota is still unknown. Methods In this study, The fecal samples were provided by healthy volunteers and hyperuricemia (HUA) patients. Fecal samples from healthy volunteers was regarded as the NOR group. Similarly, 10% HUA fecal suspension was named as the HUA group. Then, fecal supernatant was inoculated into a growth basal medium containing glucose or KGM, and healthy fecal samples were designated as the NOR-GLU and NOR-KGM groups, while HUA fecal samples were designated as the HUA-GLU and HUA-KGM groups. All samples were cultured in an anaerobic bag system. After fermentation for 24 h, the samples were collected for further analysis of composition of intestinal microbiota, SCFAs concentration and XOD enzyme activity. Results The results showed that KGM could be utilized and degraded by the gut microbiota from HUA subjects, and it could modulate the composition and structure of their HUA gut microbiota to more closely resemble that of a healthy group. In addition, KGM showed a superior modulated effect on HUA gut microbiota by increasing Megasphaera, Faecalibacterium, Lachnoclostridium, Lachnospiraceae, Anaerostipes, and Ruminococcus levels and decreasing Butyricicoccus, Eisenbergiella, and Enterococcus levels. Furthermore, the fermentation solution of KGM showed an inhibitory effect on xanthine oxidase (XOD) enzyme activity, which might be due to metabolites such as SCFAs. Conclusion In conclusion, the effect of KGM on hyperuricemia subjects was investigated based on the gut microbiota in vitro. In the present study. It was found that KGM could be metabolized into SCFAs by HUA gut microbiota. Furthermore, KGM could modulate the structure of HUA gut microbiota. At the genus level, KGM could decrease the relative abundances of Butyricicoccus, Eisenbergiella, and Enterococcus, while Lachnoclostridium and Lachnospiraceae in HUA gut microbiota were significantly increased by the addition of KGM. The metabolites of gut microbiota, such as SCFAs, might be responsible for the inhibition of XOD activity. Thus, KGM exhibited a superior probiotic function on the HUA gut microbiota, which is expected as a promising candidate for remodeling the HUA gut microbiota.